2015
DOI: 10.1080/19420862.2015.1123365
|View full text |Cite
|
Sign up to set email alerts
|

Understanding differences between synthetic and natural antibodies can help improve antibody engineering

Abstract: Synthetic libraries are a major source of human-like antibody (Ab) drug leads. To assess the similarity between natural Abs and the products of these libraries, we compared large sets of natural and synthetic Abs using "CDRs Analyzer," a tool we introduce for structural analysis of Ab-antigen (Ag) interactions. Natural Abs, we found, recognize their Ags by combining multiple complementarity-determining regions (CDRs) to create an integrated interface. Synthetic Abs, however, rely dominantly, sometimes even exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…It has been shown that in naturally occurring antibodies, CDRs specialize in certain types of contacts (Burkovitz and Ofran, 2016;Kunik and Ofran, 2013;Kunik et al, 2012b). Thus, rather than relying on random mutagenesis, library design was based on analysis of the structure and sequence of the antibody.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in naturally occurring antibodies, CDRs specialize in certain types of contacts (Burkovitz and Ofran, 2016;Kunik and Ofran, 2013;Kunik et al, 2012b). Thus, rather than relying on random mutagenesis, library design was based on analysis of the structure and sequence of the antibody.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the fact that Asp 114 is likely to form a salt bridge with a positively charged residue or the positively charged antigen in peptide–MHC complex. A lot of antigen–antibody interfaces include one or more salt bridges ( 34 ). The S118A mutation, which removes a single side chain hydroxyl group, eliminated the antigen response, illustrating the significant impact that small structural changes can have on T cell recognition.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR-amplified V H and V L and V H -C H and V L -C L gene fragments are ligated in a suitable phagemid for single-chain variable fragment (scFv) and Fab library generation, respectively. In the case of synthetic antibody phage libraries, the initial few steps are not needed, and library diversity is increased through the precise introduction of degenerate DNA into CDR encoding regions, thus rivaling or exceeding than that of natural immune repertoire [5].…”
Section: Antibody Phage Display Library Construction and Biopanningmentioning
confidence: 99%
“…Antibodies 2020, 9, x FOR PEER REVIEW 3 of 13 fragment (scFv) and Fab library generation, respectively. In the case of synthetic antibody phage libraries, the initial few steps are not needed, and library diversity is increased through the precise introduction of degenerate DNA into CDR encoding regions, thus rivaling or exceeding than that of natural immune repertoire [5]. The engineered phagemids are transformed into suitable bacteria (e.g., XL1-Blue, TG1, and ER2537), providing a suitable environment for recombination of antibody fragments [6].…”
Section: Antibody Phage Display Library Construction and Biopanningmentioning
confidence: 99%